The Effect of Soaking Time on The Quality of Candied Papaya - Khairani, Ulva; Faridah, Anni; Holinesti, Rahmi; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
One processing technology that can be developed to extend the shelf life of papaya fruit is processing papaya into sweets. Candied fruit is a type of snack made from fruit that is processed using granulated sugar and has a sweet and sour taste so it has a distinctive taste. This research aims to analyze the effect of soaking time of 3 hours, 6 hours and 9 hours on the quality of shape, color, aroma, texture and taste. This type of research is a true experiment (pure experiment) using a completely randomized design (CRD) method with 5 panelists. The data in this research uses primary data. The data was then analyzed using analysis of variance (ANOVA), if F calculated > F table then continued with the Duncan test. The results of this research are that there is no significant influence of the length of soaking on the quality of shape (neat flower shape), color (reddish yellow), aroma (typical of papaya), texture (brittle), and there is a significant influence of the length of soaking on the quality of the sweet taste. in candied papaya because F count > F table. The highest overall achievement scores were shape (neat flower shape) 4.07 (3 hours), color (reddish yellow) 4.53 (3 and 9 hours), aroma (typical papaya) 4.60 (9 hours), texture (brittle ) 4.53 (9 hours) and taste (sweet) 4.47 (9 hours). The best quality results for sweets were in the X3 treatment (9 hours).